Polymerization of Acrylonitrile Initiated by the Cerium(IV)-Glutamine Redox System: A Kinetic Study - Nagendra Kumar, K.M.; Rai, K.S. (Asian Journal of Chemistry, 2012)
Polymerization of acrylonitrile monomer [M], initiated by the free radicals formed in situ in cerium(IV)-glutamine [SH+] redox system, was studied in aqueous sulphuric acid medium in the temperature range 30-50 ºC. The rate of polymerization (Rp) and the rate of cerium(IV) disappearance have been measured. The influence of varying [M], [SH+] and [Ce4+] was examined. The effects of some water miscible organic solvents and surfactants on the rate of polymerization were investigated. The temperature dependence of the rate was studied and the activation parameters were computed using Arrhenius and Eyring plots. A mechanism consistent with the experimental data involving cerium(IV)-glutamine complex formation which generates free radicals was suggested. The chain termination step of polymerization reaction was completed by mutual interaction of free radicals.